Rural single mothers entrepreneurship program (RuSMEP) - Hashim, Norashidah; Yusof, Rohana; Abdullah, Norehan; Ayoup, Hazeline (2018)
The aim of this project is to provide support for single mothers in economic and social aspects through entrepreneurship education.The objectives of the program are to identify the single mothers who has potential to become successful entrepreneurs, examine the level of entrepreneurial readiness among single mothers, disseminate knowledge and information regarding entrepreneurship development, train and guide them with the entrepreneurship knowledge and skills. Therefore, in the long run, the participants of this program would be able to increase income and overcome poverty.The methodology used for this program was multiple approach such as psychometric test, training, coaching and mentoring. In specific, to identify the participants of single mothers through networking and purposive sampling. The survey method using structured questionnaire used in order to identify the entrepreneurial needs of single mothers. Then, designing the training program that suit with single mothers. Followed by training seminar for more than 120 participants in order to disseminate knowledge and information regarding entrepreneurship development.Pre-and-post psychometric test used to identify the level of entrepreneurship readiness among the single mothers.The final stage were coaching and mentoring for selected 25 participants among single mothers to become successful entrepreneurs with knowledge and skill. At the end of the program, most participants increase their level of income and productivity and able to decrease their production cost. Indirectly, this program also boost the participants’ self esteem, self-efficacy and entrepreneurial mind.Additionally, through this project, a database for single mothers has been developed.It also established benchmark for entrepreneurship development in rural areas.